Heart rate variability affected by radiofrequency electromagnetic field in adolescent students. Issue 4 (22nd February 2018) - Misek, Jakub; Belyaev, Igor; Jakusova, Viera; Tonhajzerova, Ingrid; Barabas, Jan; Jakus, Jan
Abstract : This study examines the possible effect of radiofrequency (RF) electromagnetic fields (EMF) on the autonomic nervous system (ANS). The effect of RF EMF on ANS activity was studied by measuring heart rate variability (HRV) during ortho‐clinostatic test (i.e., transition from lying to standing and back) in 46 healthy grammar school students. A 1788 MHz pulsed wave with intensity of 54 ± 1.6 V/m was applied intermittently for 18 min in each trial. Maximum specific absorption rate (SAR10 ) value was determined to 0.405 W/kg. We also measured the respiration rate and estimated a subjective perception of EMF exposure. RF exposure decreased heart rate of subjects in a lying position, while no such change was seen in standing students. After exposure while lying, a rise in high frequency band of HRV and root Mean Square of the Successive Differences was observed, which indicated an increase in parasympathetic nerve activity. Tympanic temperature and skin temperature were measured showing no heating under RF exposure. No RF effect on respiration rate was observed. None of the tested subjects were able to distinguish real exposure from sham exposure when queried at the end of the trial. In conclusion, short‐term RF EMF exposure of students in a lying position during the ortho‐clinostatic test affected ANS with significant increase in parasympathetic nerve activity compared to sham exposed group. Bioelectromagnetics. 39:277–288, 2018. © 2018 Wiley Periodicals, Inc.